IMPLEMENTASI KEBIASAAN MEMBACA BHAGAVAD GITA DALAM MEMBANGUN KARAKTER RELIGIUS SISWA HINDU SMPN 3 MUNCAR - Nurcahyo, Andrian Dwi; Astuti, Ni Luh Putu Wiardani; Setyaningsih (Widya Aksara : Jurnal Agama Hindu, 2024)
This study aims to implement and find out the inhibiting factors, supports, and results of the implementation of the habit of reading the Bhagavad Gita through learning Hindu Religious Education in building religious character in Hindu students at SMP Negeri 3 Muncar, Banyuwangi Regency. The research method used is qualitative descriptive through primary primary data sources; observations, interviews, documentation, and secondary supporting data; literature. Practically, the data analysis techniques of this research are described according to the stage of implementation, namely: (1) data collection techniques; (2) data reduction techniques; (3) data presentation techniques; and (4) conclusion drawing techniques. The implementation of this research is carried out through the preliminary stage of the Bhagavad Gita, the stage of the procedure for reading the Bhagavad Gita, and the stage of the meaning of reading the Bhagavad Gita. The inhibiting factors found were the lack of availability of the Bhagavad Gita, the lack of motivation to read the Bhagavad Gita, the influence of the students' social environment, and the untimely use of mobile phones. Meanwhile, the supporting factors were found due to the support of the Acting Head, Deputy Head, and Hindu Religious Education teachers of SMPN 3 Muncar, the support of the parents of Hindu students of SMPN 3 Muncar, the active role of Hindu students of SMPN 3 Muncar, and the availability of Hindu Religious Education learning rooms. As a result of the implementation of this research, the Hindu students of SMPN 3 Muncar gradually began to have a religious character with an open mindset, good manners, and obedience to the tri sandhya prayer.